Performance Ranks, Conformity, and Cooperation: Evidence from a Sweater Factory - Ashraf, Anik (Management Science, 2026)
Performance ranking can trigger multiple social incentives for workers. On one hand, it offers status rewards to induce them to increase effort. On the other, better-ranked workers may reduce effort to conform to coworkers’ productivity in fear of social retribution. This paper uses a field experiment in a sweater factory to disentangle the incentives underlying performance ranks. Treated workers receive ranks either privately or publicly. I find that private ranks do not have any effect on average but that public ranks reduce worker productivity. Additional evidence confirms that productivity declines because of workers’ social concerns and their desire to conform to the productivity of their friends. Cooperation between workers decreases too but with limited effect on productivity. The paper illustrates how inducing worker competition may be counterproductive for firms. This paper was accepted by Marie Claire Villeval, behavioral economics and decision analysis. Funding: Financial support from the Private Enterprise Development in Low-Income Countries, Centre for Economic Policy Research [PEDL ERG 4362] and the DFG through CRC TRR 190 [Project 280092119] are gratefully acknowledged. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.01381 .